2007
DOI: 10.1016/j.neulet.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal localization of injury potentials in DRG neurons during vincristine-induced axonal degeneration

Abstract: The distal to proximal degeneration of axons, or "dying back" is a common pattern of neuropathology in many diseases of the PNS and CNS. A long-standing debate has centered on whether this pattern of neurodegeneration is due to an insult to the cell body or to the axon itself, although it is likely that mechanisms are different for specific disease entities. We have addressed this question in a model system of vincristine-induced axonal degeneration. Here, we created a novel experimental apparatus combining a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 17 publications
2
18
0
1
Order By: Relevance
“…In agreement with our observations, axonal degeneration, IENF decrease or sensory terminal arbor dysregulation have previously been described in antineoplastic-treated animals or patients [12,34,35]. However, VINC-induced down-regulation of CNPase expression in peripheral nerves in vivo has never been demonstrated, and the present report constitutes the first one providing this crucial information.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our observations, axonal degeneration, IENF decrease or sensory terminal arbor dysregulation have previously been described in antineoplastic-treated animals or patients [12,34,35]. However, VINC-induced down-regulation of CNPase expression in peripheral nerves in vivo has never been demonstrated, and the present report constitutes the first one providing this crucial information.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the amplitude of the MCAP was significantly decreased, while its duration was significantly prolonged in the VCR group. This suggests that a significant number of sensory and motor fibers are affected by the drug as confirmed by reported histological studies, which showed VCR-induced axonal degeneration as well as disorganization of the axonal microtubule cytoskeleton and increase in the caliber of unmyelinated sensory axons (9,16). On the other hand, no significant change was observed in conduction velocity.…”
Section: Discussionsupporting
confidence: 63%
“…"Axonal" hypotheses postulated that the degenerative process is triggered in the axon itself: Vincristine, a chemotherapeutic agent used in human cancer therapy, causes a peripheral neuropathy with prominent distal axonal degeneration (Bradley et al, 1970). The axonal dying back process can be mimicked in neuronal cultures (Ravula et al, 2007) in which topic application of Vincristine at clinically relevant concentrations injures the axon but not the neuronal soma (Silva et al, 2006). Several genetic studies have also linked impaired retrograde axonal transport to motor neuron degeneration.…”
Section: Subcellular Origin Of Axonal Degenerationmentioning
confidence: 99%